Effects of long-term exposure to the low-earth orbit environment on drag augmentation systems - Serfontein, Zaria; Kingston, Jennifer; Hobbs, Stephen; Impey, Susan A.; Aria, Adrianus Indrat; Holbrough, Ian E.; Beck, James C. (Elsevier, 2021)
Spacecraft in low-Earth orbit are exposed to environmental threats which can lead to material degradation and component failures. The presence of atomic oxygen and collisions from orbital debris have detrimental effects on the structures, thus affecting their performance. Cranfield University has developed a family of drag augmentation systems (DAS), for end-of-life de-orbit of satellites, addressing the space debris challenge and ensuring that satellites operate responsibly and sustainably. De-orbit devices are stowed on-orbit for the duration of the mission lifetime and, once deployed, the devices must withstand the harsh low Earth environment until re-entry; a process which can take several years. The DAS’ deployable aluminised Kapton sails are particularly susceptible to undercutting by atomic oxygen. In preparation for commercialising the DAS, Cranfield University are investigating the degradation process of the drag sail materials, with the end goal of qualifying the materials for the specific application of drag sails in low Earth orbit (LEO). This paper will outline the proposed research and the expected benefits from the projects. This paper will conclude in a summation of the different on-going research projects at Cranfield University related to commercialising the DAS family. This research will benefit the wider space community by expanding the understanding of the effects of long-term exposure on certain materials, as well as improving the validity of future low Earth atmospheric models.
Keywords: Space debris; Drag sails; Low earth orbit; Material degradation; Aluminised kapton; Atomic oxygen undercutting